Whither corruption? A quantitative survey of the literature on corruption and growth - Nauro F. Campos; Ralitza Dimova; Ahmed Saleh (Institute for the Study of Labor (IZA), 2010)
Does corruption grease or sand the wheels of economic growth? This paper uses metaanalysis techniques to systematically evaluate the evidence addressing this question. It uses a data set comprising 460 estimates of the effect of corruption on growth from 41 empirical studies. The main factors explaining the variation in these estimates are whether the model accounts for institutions and trade openness (both are found to deflate the negative effect of corruption), authors' affiliation (academics systematically report less negative impacts), and use of fixed-effects. We also find that publication bias, albeit somewhat acute, does not eliminate the genuine negative effect of corruption on economic growth.
Keywords: O1; 330; corruption; economic growth; meta-regression analysis